Kajian Kinerja Kombinasi Filler Tanah Putih dan Abu Sekam Padi pada Campuran Aspal AC-WC - Anastasia Ipah Wuwur, Dewi; Budiman Pantas, Vinsensius; Rikardus Sodanango, Mateus; Bernadus Mbau, Reza (Jurnal Manajemen Teknologi & Teknik Sipil, 2025)
The high cost and limited availability of conventional fillers in several regions necessitate the exploration of local alternative materials. This study investigates the potential use of white soil (limestone) and rice husk ash (RHA) as alternative fillers in Asphalt Concrete–Wearing Course (AC-WC) mixtures. The experimental research was conducted at the Kupang State Polytechnic Laboratory. White soil was sourced from East Penfui, while rice husk ash was collected from Oesao. Filler variations of 0%, 0.5%, 1%, 1.5%, and 2% were tested on 63 specimens in accordance with Bina Marga 2018 specifications. Marshall tests were performed to evaluate stability, VIM, VMA, VFA, flow, and MQ parameters. The results show that white soil filler optimally increased density and achieved desirable VIMand VMA values up to 1.5%, while rice husk ash enhanced flexibility but tended to increase voids at higher percentages. The optimum combination of both fillers was found at 0.75% total filler content, fulfilling all Marshall parameter standards specified by Bina Marga 2018. This study concludes that a carefully optimized combination of white soil and RHA is a viable, economical, and sustainable alternative filler for AC-WC pavement layers.